Pengelolaan Ekosistem Mangrove Sebagai Upaya Mitigasi Bencana di Provinsi Aceh - Made Dwipa Kusuma Maharani; Jasmine Masyitha Amelia; Gressty Sari Br Sitepu (Jurnal Pendidikan Biologi Undiksha, 2022)
Earthquake of magnitude 9,1-9,3 SR followed by the tsunami caused a damage of mangrove ecosystems and infrastructure in almost all coastal areas of Aceh Province. In this study the data taken are the density, frequency,acover, important value index, diversity index, equitability index, dominance index.and mitigation efforts conducted.by direct interview. The results of this study showed that the species found were Rhizophora apiculata, Rhizophora mucronata, Bruguiera gymnorizha, Ceriops tagal, Avicennia marina, Xylocarpus granatum, Lumnitzera littorea and.Sonneratia caseolaris. Of all mangrove species that found, the type that dominates in almost all stations is Rhizophora apiculata. Mitigation strategy in reducing tsunami threat by maintaining mangrove ecosystem, addition of mangrove ecosystem area and habitat and increasing density. The density used is 1.5 x 1.5 meter and 1 x 1 meter. The local agency has rehabilitated approximately 4,076.25 Ha of mangrove forest area that was once carried by tsunami waves.